2021
DOI: 10.5624/isd.20200191
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CBCT metal artifact reduction on vertical radicular fracture detection

Abstract: Purpose This study evaluated the influence of a metal artifact reduction (MAR) tool in a cone-beam computed tomography (CBCT) device on the diagnosis of vertical root fractures (VRFs) in teeth with different root filling materials. Materials and Methods Forty-five extracted human premolars were classified into three subgroups; 1) no filling; 2) gutta-percha; and 3) metallic post. CBCT images were acquired using an Orthopantomograph 300 unit with and without a MAR tool. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 38 publications
1
14
2
Order By: Relevance
“…These results were consistent with many studies that reported excellent agreement for the accuracy of detection of vertical root fracture on CBCT in the presence of metal artifact. (30,(32)(33)(34) , However, our results disagree with Oliveira et al (35) , who reported low levels of interobserver reproducibility which they attributed to the voxel size used in their study (0.085mm) where partial volume averaging might have limited the viewing of delicate vertical fracture lines.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These results were consistent with many studies that reported excellent agreement for the accuracy of detection of vertical root fracture on CBCT in the presence of metal artifact. (30,(32)(33)(34) , However, our results disagree with Oliveira et al (35) , who reported low levels of interobserver reproducibility which they attributed to the voxel size used in their study (0.085mm) where partial volume averaging might have limited the viewing of delicate vertical fracture lines.…”
Section: Discussioncontrasting
confidence: 99%
“…This indicates that the presence of metal artifacts in general has the ability to reduce the diagnostic ability of CBCT images Moreover, artifact reduction algorithm improved the diagnostic accuracy of CBCT in implant group than the implant group without AR algorithm (95.0% versus 91.7% respectively), which comes in agreement with Freitas et (20) , Candemil et al (30) , Al Hadi et al (32) , Uysal et al (33) , Abd-Elsattar et al (34) and Hekmatian et al (36) . These diagnostic accuracy results also disagree with Oliveira et al (35) , who reported that the activation of MAR tool reduced the diagnostic accuracy of CBCT of vertical root fracture more than when MAR tool was deactivated. Their findings might be attributed to the use of small FOV (6x4 cm) and small voxel size (0.085 mm) which might result in higher signal-to-noise ratio and as MAR works by reducing the grey value of image, it was difficult under these circumstances to detect the hypodense fracture line against normal tooth structure.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…According to Nikneshan et al (10) the diagnostic sensitivity and specificity without MAR were higher than the values in the presence of MAR (10). Oliveira et al (11) concluded that application of MAR had a negative effect on the detection of VRF in teeth without root canal filling, and in teeth with gutta-percha root filling material, and metal posts. De Rezende Barbosa et al (12) reported that applying MAR did not improve the diagnosis of VRFs.…”
Section: Discussionmentioning
confidence: 99%
“…For the detection of VRFs, the image quality should be high enough to reconstruct the hypodense fracture line in contrast to the adjacent structures. CBCT image quality is affected by a number of different factors, such as FOV (a large FOV has lower contrast and spatial resolution than a small FOV), voxel size, signal/noise ratio, contrast, spatial resolution, scattering, artifacts, detector quality, and image reconstruction algorithms (11). Voltage (kVP) is among the most influential parameters on artifact generation, probably because it is responsible for the energy level of photons.…”
Section: Discussionmentioning
confidence: 99%